Area postrema syndrome as frequent feature of Bickerstaff brainstem encephalitis. Issue 12 (31st October 2018) - Zeiner, Pia S.; Brandhofe, Annemarie; Müller‐Eschner, Monika; Steinmetz, Helmuth; Pfeilschifter, Waltraud
Abstract: Objective: Area postrema (AP) syndrome (defined as: nausea and/or emesis and/or singultus at onset of brainstem dysfunction) comprises complex pathophysiologic mechanisms triggered by different entities. The first objective was to assess the frequency of AP syndrome as a clinical feature in brainstem encephalitis (BE). Finding an especially high prevalence of AP syndrome in Bickerstaff brainstem encephalitis (BBE), we also analyzed the frequency of AP syndrome in other autoimmune diseases with anti‐ganglioside antibodies (Guillain–Barré syndrome (GBS) and its variants). Methods: We systematically evaluated the prevalence of AP syndrome in BE in all patients treated at our university hospital during a 15‐year period. In a second step, BBE patients were compared to GBS and Miller Fisher syndrome (MFS) patients as clinical subtypes of a disease continuum without brainstem dysfunction. Results: We found AP syndrome in 8 of 21 BE patients, including 3 of 7 BBE and in 4 of 112 GBS/MFS patients. AP syndrome was as a frequent but under‐recognized feature of BE with a significant impact on patients' well being. Interpretation: Manifestation of AP syndrome in BBE but also in GBS and its subtypes point toward a role of autoimmune antibodies that should be investigated in future studies. Considerable misdiagnosis or nonrecognition complicates diagnostic and therapeutic management. Therefore, AP syndrome should be considered in any episode of otherwise unexplained nausea, emesis, or singultus.